Dampak Media Sosial Terhadap Perilaku Siswa Di Madrasah Aliyah Swasta Pinogaluman, Kabupaten Bolaang Mongondow Utara - Ngiu, Zulaecha; Nggilu, Ariyanto; Pandi, Muhammad Taufik M (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The impact of social media such as YouTube, WhatsApp, Tiktok, Instagram, Facebook and so on has positive and negative impacts on students. Positive impacts, for example, will have creativity, have innovation in the development of science, and be used as an online business. The negative impact of foreign culture on students has reached an alarming stage because there is a tendency for students to have forgotten the culture of their own people. The culture of following along with Appearance or how to dress, following tick-tock trends, style of language in speaking, and shopping online, and always playing online games will affect the volume of brain cells so that the level of intelligence will decrease. Based on the above problems, the researchers conducted outreach to students in the private Madrasah Aliyah Hall, Pinogaluman District, North Bolaang Mongondow Regency with the aim of (1) strengthening and inculcating national character values for students in private Madrasah Aliyah, Pinogaluman District, Regency Bolaang Mongondow Utara. (2) Increasing students' awareness of their behavior while in the Madrasah environment. (3) Building a good cooperative relationship between teachers and parents of students. After carrying out the Mentoring and Socialization activities for students, we plan to do a mapping to find out how successful the teacher is in guiding his students.